Senegal : Request for a Three-Year Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Senegal's Request for a Three-Year Policy Support Instrument (PSI). Performance under the two previous PSIs was mixed. The new PSI aims to support a three-year program of macroeconomic reforms designed to advance the authorities' growth strategy-Plan Senegal Emergent (PSE). The growth goals enshrined in the PSE are achievable provided reforms are successfully implemented. Early signs indicate positive momentum owing to observed progress in reform implementation and favorable external factors. However, more remains to be done to solidify this momentum. Also, there are significant but manageable risks, which include sluggish implementation of reforms and election-driven pressures in 2016 and 2017. The IMF staff supports the authorities' request for a PSI.